Principals’ Capacity Building Skills and Teachers’ Job Performance in Senior Secondary Schools in Plateau State, Nigeria - Ndupuechi, Timson Ifeanyi I. (NIU Journal of Social Sciences, 2019)
The title of the paper is the relationship between the principals’ capacity building skills and teachers’ job performance in senior secondary schools in Plateau state, Nigeria. The problem of abysmal students’ academic performance in Senior Secondary School Certificate Examinations (SSCE) particularly in English and Mathematics in Plateau State, Nigeria, which has apparently been attributed to the principals’ capacity building skills and teachers’ job performance has been something of great concern to education stakeholders. The discouraging situation has deprived these students opportunity of getting admission into tertiary institutions. It is believed that if the situation is not checked the productive capability of youths will be negatively affected and national development retarded.  The aim and objective of the paper was to find out the nature of principals’ capacity building skills in relation to Teachers’ job performance. The research design adopted for the study was correlational type, since the aim of the study was to find out the relationship between dependent and independent variables . The population of the study was made up of 303 principals and 870 teachers. A sample of 174 principals which represent 57% of the principals and 487 teachers representing 56% of the teachers were taken. The results of the study showed that principals have adequate capacity building skills. Some of the recommendations are that efforts should be made by the Nigerian governments (Federal and States) and other education stakeholders to make resources available to enable both Principals and Teachers attend more seminars, workshops and conferences. Also training and retraining of teachers should be encouraged. By these Principals and Teachers will be in tune with the dynamics and teaching strategies of the 21 st century Keywords: Principals' Capacity Building Skills, Teachers Job Performance and Secondary Schools